Unraveling the Factors Affecting the Electrochemical Performance of MoS 2 -Carbon Composite Catalysts for Hydrogen Evolution Reaction: Surface Defect and Electrical Resistance of Carbon Supports - Hyeon, Yuhwan; Jung, Su Ho; Jang, Wonseok; Kim, Mansu; Kim, Byung Sung; Lee, Jae Hyun; Nandanapalli, Koteeswara Reddy; Jung, Namgee; Whang, Dongmok (ACS Applied Materials and Interfaces, 2019)
In MoS 2 -carbon composite catalysts for hydrogen evolution reaction (HER), the carbon materials generally act as supports to enhance the catalytic activity of MoS 2 nanosheets. The carbon support provides a large surface area for increasing the MoS 2 edge site density, and its physical structure can affect the electron transport rate in the composite catalysts. However, despite the importance of the carbon materials, direct observation of the effects of the physical properties of the carbon supports on the HER activity of MoS 2 -carbon composite catalysts has been hardly reported. In this work, we conduct an experimental model study to find the fundamental and important understanding of the correlation between the structural characteristics of carbon supports and the HER performance of MoS 2 -carbon composite catalysts using surface-modified graphitic carbon shell (GCS)-encapsulated SiO 2 nanowires (GCS@SiO 2 NWs) as support materials for MoS 2 nanosheets. The surface defect density and the electrical resistance of GCS@SiO 2 NWs are systematically modulated by control of H 2 gas flow rates during the carbon shell growth on the SiO 2 NWs. From in-depth characterization of the model catalysts, it is confirmed that the intrinsic catalytic activity of MoS 2 -carbon composites for the HER is improved linearly with the conductance of the carbon supports regardless of the MoS 2 edge site density. However, in the HER polarization curve, the apparent current density increases in proportion to the product of the number of MoS 2 edge sites and the conductance of GCS@SiO 2 NWs.
Keywords: Carbon composites; Carbon support; Electrical resistances; Electrochemical performance; Electron transport rate; Experimental modeling; Hydrogen evolution reactions; Structural characteristics; carbon support; electrical resistance; hydrogen evolution reaction; MoS 2 -carbon composite catalyst; surface defect